1965
DOI: 10.1136/jcp.18.4.408
|View full text |Cite
|
Sign up to set email alerts
|

Histological findings in the Paterson-Kelly syndrome

Abstract: SYNOPSIS Forty-one specimens taken from lesions in the post-cricoid region of patients with the Paterson-Kelly syndrome have been examined. Most Forty-one specimens were obtained from post-cricoid lesions in 39 patients. The specimens were mostly small and contained epithelium and subepithelial elements superficial to the main muscular layers. In five instances, the biopsies consisted of epithelium alone. Deeper tissues were present in specimens from four necropsies, but in only one biopsy.Paraffin sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Dysphagia had been present for 30 years, but determination of whether the web was congenital is difficult. The pathophysiology of plication in patients diagnosed with esophageal web reportedly comprises the growth of connective tissues in the lamina propria, infiltration of lymphocytes, 6 and in this case the web surface was covered with mucosal carcinoma. Although the tumor in the posterior cervical esophageal wall was regional squamous cell carcinoma, it is difficult to determine whether this tumor originated from the web, or whether an esophageal carcinoma infiltrating into the mucosal layer de novo resulted in formation of the web.…”
Section: Discussionmentioning
confidence: 84%
“…Dysphagia had been present for 30 years, but determination of whether the web was congenital is difficult. The pathophysiology of plication in patients diagnosed with esophageal web reportedly comprises the growth of connective tissues in the lamina propria, infiltration of lymphocytes, 6 and in this case the web surface was covered with mucosal carcinoma. Although the tumor in the posterior cervical esophageal wall was regional squamous cell carcinoma, it is difficult to determine whether this tumor originated from the web, or whether an esophageal carcinoma infiltrating into the mucosal layer de novo resulted in formation of the web.…”
Section: Discussionmentioning
confidence: 84%
“…It is known that the histology of a postcricoid web is essentially that of a fold of normal oesophageal epithelium with some underlying loose connective tissue. 11 We contemplate that the web had become less prominent after its epithelial layer sloughed off along with the oesophageal cast.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic webs are more often found in females and if associated with iron-deficiency anemia, koilonychias, and glossitis can be associated with Plummer-Vinson or Patterson-Kelly syndromes (2,6). Webs usually consist of mucosa and submucosa and involve a connective tissue band covered with normal epithelium (3). The exact etiology is not known, but it has been suggested that they occur as a consequence of incomplete vacuolization of esophageal columnar epithelium during embryological development (14).…”
Section: Discussionmentioning
confidence: 99%